Ocular Dominance Plasticity in Binocular Primary Visual Cortex Does Not Require C1q - Christina A. Welsh; Céleste-Élise Stephany; Richard W. Sapp; Beth Stevens (2019)
C1q, the initiator of the classical complement cascade, mediates synapse elimination in the postnatal mouse dorsolateral geniculate nucleus of the thalamus and sensorimotor cortex. Here, we asked whether C1q plays a role in experience-dependent synaptic refinement in the visual system at later stages of development. The binocular zone of primary visual cortex (V1b) undergoes spine loss and changes in neuronal responsiveness following the closure of one eye during a defined critical period [a process referred to as ocular dominance plasticity (ODP)]. We therefore hypothesized that ODP would be impaired in the absence of C1q, and that V1b development would also be abnormal without C1q-mediated synapse elimination. However, when we examined several features of V1b development in mice lacking C1q, we found that the densities of most spine populations on basal and proximal apical dendrites, as well as firing rates and ocular dominance, were normal. C1q was only transiently required for the development of spines on apical, but not basal, secondary dendrites. Dendritic morphologies were also unaffected. Although we did not observe the previously described spine loss during ODP in either genotype, our results reveal that the animals lacking C1q had normal shifts in neuronal responsiveness following eye closure. Experiments were performed in both male and female mice. These results suggest that the development and plasticity of the mouse V1b is grossly normal in the absence of C1q. SIGNIFICANCE STATEMENT These findings illustrate that the development and experience-dependent plasticity of V1b is mostly normal in the absence of C1q, even though C1q has previously been shown to be required for developmental synapse elimination in the mouse visual thalamus as well as sensorimotor cortex. The V1b phenotypes in mice lacking C1q are more similar to the mild defects previously observed in the hippocampus of these mice, emphasizing that the contribution of C1q to synapse elimination appears to be dependent on context.